IMPROVEMENT OF INDONESIAN LANGUAGE LEARNING PROCESS AND OUTCOMES USING A TEAMS GAMES TOURNAMENT TYPE COOPERATIVE LEARNING MODEL IN GRADE IV SDN 100/II MUARA BUNGO: PENINGKATAN PROSES DAN HASIL BELAJAR BAHASA INDONESIA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DI KELAS IV SDN 100/II MUARA BUNGO - Fathiya Salsabila; Aprizan; Zulqoidi R Habibie (SOSIOEDUKASI, 2025)
P This research aims to improve the process and outcomes of Indonesian learning through the application of a cooperative learning model of the Teams Games Tournament (TGT) type in grade IV of SDN 100/II Muara Bungo. The research method used is Class Action Research (PTK) which is carried out in two cycles. The research subjects amounted to 26 students. Data was collected through observation, learning outcome tests, and documentation. The results of the study showed a significant improvement in both process aspects and learning outcomes. In the first cycle, the achievement of student learning outcomes was 72% with the adequate category, while in the second cycle it increased to 88% with the good category. The application of the TGT model has been proven to be able to create a more active, interactive, and fun learning atmosphere, so that it can increase students' motivation and learning outcomes in Indonesian subjects.